Evaluating the impact of a virtual reality workstation in an academic library: Methodology and preliminary findings. Issue 1 (1st February 2019) - Lischer‐Katz, Zack; Cook, Matt; Boulden, Kristal
ABSTRACT: Collections of 3D models and the analytic affordances of virtual reality (VR) systems can be integrated to form a "3D digital heritage ecosystem" (Limp, et al., 2011), providing a potentially richer and more intuitive learning environment that enables students to interact with models of artifacts and spaces that are too rare, fragile, or distant to access directly. This paper describes efforts to evaluate the impact of virtual reality on undergraduate instruction in varied disciplines, hosted within an academic library context. Existing research on VR and learning has focused primarily on domain‐specific tasks carried out in controlled lab settings or the social aspects of immersive virtual worlds. This paper describes the methodology and preliminary findings of a mixed‐methods research project currently underway (running from September 2017 to August 2018) that is evaluating how use of virtual reality impacts undergraduate students' self‐efficacy, and seeks to understand students' embodied experiences. The strengths and weaknesses of the methodology, initial findings drawn from the early stages of data analysis, and directions for further research are discussed.